Regulation of fatty acid delivery in vivo. - Frayn, K (1998)
Adipose tissue triacylglycerol (TG) constitutes by far the largest energy store in the body. In order for this TG to be used as a substrate for oxidative metabolism, it has to be exported from adipose tissue and transported to the tissues where it will be used. Following hydrolysis of stored TG, non-esterified fatty acids (NEFA) leave the adipocyte and enter the plasma. Unlike tissues such as skeletal muscle which extract plasma NEFA, in adipose tissue the flow of fatty acids across the cell membrane is bi-directional, outward in times of net fat mobilization such as fasting and exercise, and inward during the postprandial period. Factors regulating NEFA delivery in vivo include hormonal and nervous stimulation of lipolysis, and a variety of factors, local and systemic, which oppose this by suppressing lipolysis. Adipose tissue blood flow (ATBF) is also important. ATBF is increased in states of fat mobilization and fat deposition, although there is evidence that during strenuous exercise the increase in ATBF is not sufficient for export of all the NEFA made available from lipolysis. There are well-documented regional variations in lipolysis. The intra-abdominal depots appear to have the highest rates of TG turnover, the subcutaneous abdominal an intermediate rate, and the gluteal-femoral depots to have relatively sluggish turnover. However, much of the evidence for this derives from studies of isolated adipocytes, and confirmation in vivo is much needed. There are links between abdominal fat deposition and risk of cardiovascular disease which may be mediated through increased fatty acid delivery from abdominal fat depots. The ability of exercise specifically to decrease intra-abdominal fat stores may be yet another health benefit of regular exercise.